PENGARUH PROFESIONALISME GURU PAK TERHADAP DISIPLIN BELAJAR SISWA KELAS VIII SMP NEGERI 2 LUMBANJULU TAHUN 2017/2018 - Marta Simanjuntak (IAKN Tarutung, 2018)
Abstract, This Research aim to to know the influence of Teacher Professionalism PAK To Discipline Leart The Student Of Class of VIII SMP Country 2 Lumbanjulu of Regency of Toba Samosir of Study Year 2017/2018. With the hypothesizining of there are influence which are positive and signifikan of among/between Teacher Professionalism PAK To Discipline Leart The Student Of Class of VIII SMP Country 2 Lumbanjulu of Regency of Toba Samosir of Study Year 2017/2018. Research population amount to 1345 people and sampel amount to44 people. Data collected with the enquette closed by as much 31 item compiledby researcher of pursuant to variable indicatot of according to expert theory. Test-Drive the instrument [done/conducted] to 30 student which is non research responder and have been tested [by] the validity and realiabilitasnya. Hasil analyse the data indicate the there are influence which are positive and signifikan of among/between Teacher Professionalism PAK To Discipline Leart The Student Of Class of VIII SMP Country 2 Lumbanjulu of Regency of Toba Samosir of Study Year 2017/2018 with the coefficient determinasi (r2 ) = 30,47% and test the signifikan influence obtained [by] Fhitung Ftabel [of]equal to 18,304,08, inferential thereby Ho refused and [is] Ha accepted. Keyword: Teacher Professionalism, Disicipline Learn